Refractive errors characteristic of the patients at the Children’s Ophthalmology Outpatient Department of Kauno klinikos Hospital (Lithuanian University of Health Sciences) from 1 January 2012 to 31 December 2012 - Čiumbaraitė, Rasa; Liutkevičienė, Rasa (Acta medica Lituanica, 2017)
Background. The purpose of our study was to assess the distribution and patterns of refractive errors in children for the proper planning of paediatric eye care at the centre. Material and methods. The study was conducted in the hospital of the Lithuanian University of Health Sciences in Kaunas, from 1 January 2012 to 31 December 2012. During this period, a total of 11,406 children, aged 0–18  years, were evaluated at the  outpatient department of paediatric ophthalmology, Kauno klinikos, the  Lithuanian University of Health Sciences. All the children underwent a complete ophthalmic examination with cycloplegic refraction. Results. Myopia increased from 1.5% (95% CI:1.2, 1.8) in the age group of 0–1 to 44.7% (95% CI:43.46, 45.94) in the age group of 14–18 (p
Keywords: myopia; hypermetropia; astigmatism